Trafficking Cinderella - Niagolova, Mira (Canada, 2001)
Since the fall of the Berlin Wall in 1989 and the resulting political and economic changes, there has been an alarming increase in forced prostitution and trafficking of women from Eastern Europe to the West and North America. While officials are still debating contradictions in the existing regulations, the structures of the international prostitution enterprise are thriving; life-threatening and security issues grow worse as thousands of women are reaching the point of no return. "Trafficking Cinderella" features the gut wrenching testimonies of broken dreams, withered illusions, rape and humiliation from several Eastern European girls sold as prostitutes throughout the world.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films